Tomato mitogen-activated protein kinase: mechanisms of adaptation in response to biotic and abiotic stresses - Shi, Yumei; Zhang, Zhifang; Yan, Zhenghao; Chu, Honglong; Luo, Changxin (Frontiers in Plant Science, 2025)
Plants live under various biotic and abiotic stress conditions, and to cope with the adversity and severity of these conditions, they have developed well-established resistance mechanisms. These mechanisms begin with the perception of stimuli, followed by molecular, biochemical, and physiological adaptive measures. Tomato (Solanum lycopersicum) is a globally significant vegetable crop that experiences several biotic and abiotic stress events that can adversely impact its quality and production. Mitogen-activated protein kinases (MAPKs) in tomato plants have crucial functions of mediating responses to environmental cues, internal signals, defense mechanisms, cellular processes, and plant development and growth. MAPK cascades respond to various environmental stress factors by modulating associated gene expression, influencing plant hormone synthesis, and facilitating interactions with other environmental stressors. Here, we review the evolutionary relationships of 16 tomato SlMAPK family members and emphasize on recent studies describing the regulatory functions of tomato SlMAPKs in both abiotic and biotic stress conditions. This review could enhance our comprehension of the MAPK regulatory network in biotic and abiotic stress conditions and provide theoretical support for breeding tomatoes with agronomic traits of excellent stress resistance.